Current status of breast cancer in Nepal - Giri, Mohan; Puri, Anju; Upreti, Bibhuti (International Journal of Research in Medical Sciences, 2019)
Breast carcinoma is one of the most common and dreaded diseases of women, and in Nepal, it is second most common cancer. The situation is more alarming in the rural areas where the majority of women are illiterate and ignorant about the hazards of breast cancer. Different screening strategies such as rural cancer registries and camp approach for cancer detection have been found useful in minimizing the problem of breast cancer in the villages. Advanced presentation of breast cancer and the problem of late diagnosis is well documented in Nepal. Moreover, diagnostic workup, treatment and palliative services are inadequate in most parts of Nepal. A better understanding current situation of breast cancer can help government to formulate breast cancer prevention strategy in Nepal. In this review, authors present an overview of the burden of breast cancer, risk factors, screening, and cancer care among Nepalese women.